2014
DOI: 10.1684/mrh.2014.0364
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperalgesic effect of systemic magnesium sulfate in carrageenan-induced inflammatory pain in rats: influence of the nitric oxide pathway

Abstract: This study investigated whether systemic magnesium sulfate (an antagonist at the glutamate subtype of N-methyl-D-aspartate receptor) affects inflammatory pain, and whether the nitric oxide pathway is involved. Carrageenan (0.5%, 0.1 mL, intraplantar)-induced mechanical hyperalgesia was evaluated using the electronic von Frey test in male Wistar rats. Magnesium sulfate had no effect when injected locally into the inflamed rat paw. However, subcutaneous magnesium sulfate, at doses of 0.5, 5, 15 and 30 mg/kg, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 35 publications
1
34
1
Order By: Relevance
“…[ 34 35 ] The other reported mechanisms for MgSO 4 were, reduce the activity of presynaptic and postsynaptic calcium channels and to modulate the release of neurotransmitters, also influencing membrane potentials by exhibits modulator effects on sodium and potassium currents. [ 11 13 ] In the other hand, ketamine interacts with calcium and sodium channels, cholinergic transmission, dopamine receptors, and anti-inflammatory effects. [ 36 ] Hence, further studies with large samples are suggested to assess the effectiveness of different doses of MgSO 4 in combination with ketamine for PSA in the emergency department setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 35 ] The other reported mechanisms for MgSO 4 were, reduce the activity of presynaptic and postsynaptic calcium channels and to modulate the release of neurotransmitters, also influencing membrane potentials by exhibits modulator effects on sodium and potassium currents. [ 11 13 ] In the other hand, ketamine interacts with calcium and sodium channels, cholinergic transmission, dopamine receptors, and anti-inflammatory effects. [ 36 ] Hence, further studies with large samples are suggested to assess the effectiveness of different doses of MgSO 4 in combination with ketamine for PSA in the emergency department setting.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium sulfate (MgSO 4 ) is an endogenous voltage-dependent NMDA receptor channel blocker. [ 11 12 ] In different types of pain in humans and animals,[ 13 14 15 ] it has been demonstrated that MgSO 4 alone has an analgesic effect. [ 16 17 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that MgSO 4 did not alter the sensitivity of parietal cells to gastrin (Christiansen, Rehfeld, & Stadil, 1975). MgSO 4 has been reported to show an anti-hyperalgesic effect involving activation of the nitric oxide pathway (Srebro, Vučković, Vujović, & Prostran, 2014) .…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, Mg ions may influence the pain through a number of diverse pathways [44] including the following: (1) decrease in NMDA action, (2) reducing the synthesis of P substance and its action in the dorsal horn, (3) potency of morphine in the presynaptic part of the dorsal horn, (4) a reduction in the action of some calcium channels in the central nervous system, and (5) a reduction in thromboxane A2 or in the synthesis of certain cytokines for the peripheral system [40,[43][44][45][46][47][48][49][50].…”
Section: Magnesium Chloridementioning
confidence: 99%
“…Chloride. Some models of pain have revealed that exogenous application of zinc has an antihyperalgesic effect [20,47,51]. Even though the Zn modulation pathways of pain are multiple and complex, it is known to control the functions of many pain-related ions channels, including ASICs [52], voltage-gated Ca 2+ and Κ + channels [53], and NMDA receptors [48,51].…”
Section: Zincmentioning
confidence: 99%